STATISTICAL EVALUATION AND OPTIMISATION OF BIODIESEL PRODUCTION FROM Gmelina arborea LEAF BIOMASS USING CALCIUM HYDROXIDE CATALYSIS UNDER MILD CONDITIONS - Ali, Abubakar M.; Shuaibu, Hadiza; Ibrahim, Haruna (FUDMA Journal of Sciences, 2026)
Amid growing demand for sustainable energy, this work explores the production of third-generation biodiesel from waste Gmelina arborea leaf biomass using calcium hydroxide as an earth-abundant heterogeneous catalyst under mild conditions. Biodiesel synthesis was systematically investigated using a Box-Behnken design with 17 runs, with yields quantified as both percentage yield and specific yield (mg/g). Biodiesel yields varied widely, ranging from 0.23 to 30.00% (17.1-1259.8 mg/g), indicating a strong dependence on synergistic interactions among operating parameters rather than on individual variables alone. Reproducibility analysis conducted under identical reaction conditions yielded a mean biodiesel yield of 6.38% with a coefficient of variation of 36.1%, indicating acceptable process stability for a heterogeneous lignocellulosic system. While one-way ANOVA indicated that temperature alone did not exert a statistically significant influence on biodiesel yield within the studied range (p > 0.05), the strong variation in yields across different parameter combinations, culminating in a peak yield of 30.00% at 50 °C, 40 min, and 2.0 wt% catalyst loading, suggests that temperature effects are highly dependent on synergistic interactions with catalyst loading and reaction time. Overall, the results demonstrate that waste leaf biomass can serve as a viable third-generation biodiesel feedstock when coupled with mild calcium hydroxide catalysis, offering an energy-efficient and sustainable pathway that minimises food-fuel competition and supports circular bioeconomy development.
Keywords: Biodiesel; Lignocellulosic; biomass; Gmelina arborea; leaves; Calcium hydroxide; catalyst; Third-generation biofuels; Waste biomass valorisation